TO TRACK ADVERSE REACTIONS, EVENTS AND INCIDENCE ASSOCIATED WITH BLOOD AND BLOOD PRODUCT TRANSFUSION: Pharmaceutical Science-Medicine - DR.PRASANNA; GANPISETTI, DR.RAMESH; SUSMITHA, DR.GADAMSETTI. (International Journal of Life Science and Pharma Research, 2019)
Haemovigilance is defined as a set of surveillance procedures covering whole transfusion chain from the collection of blood and its components to the follow up of its recipients, intended to collect and assess the information. The major aim of this study is to track adverse reactions/ events and incidence associated with blood and blood product transfusion unexpected or undesirable effects resulting from therapeutic of liable blood products. To identify hazards , risks and to provide information as to where the system is breaking down. To analyze any incidents and errors that may impact on the safety of blood products. To promote, enable and maintain a high level of ethical medical and scientific standards in blood transfusion science and medicine. which shows that the transfusion was majorly done in patients between the age group of 20-30 (29.00%) followed by 30-40 years (22.00%). The age group with the least blood transfusion was found as 40-50years (15.00%), 10-20 years (6.00%) and 0-9 years (8.00%). In our study it was observed that the PRBC administration for the patients with normal Hb levels were due to dialysis and anemic conditions. PRBC are administered in surgery cases even if they have Hb levels greater than 10 gm/dl. Pharmacist should involve in the development of local educational and training materials which is required by staff involved in transfusion procedures. Staff training should be maintained and updated with evidence of training and competency documented assessment of training should be undertaken in accordance with local and national guidelies.